Institutional Capacity Assessment Tool (ICAT) For Community Rangeland Management Institutions (RMIs) - Sircely, Jason A.; Ayehu, M.; Flintan, Fiona E. (International Livestock Research Institute, 2022)
An institutional capacity assessment tool used to score the capacity of community-level rangeland management institutions.